ANTAGONIS BAKTERI PROBIOTIK YANG DIISOLASI DARI USUS DAN LAMBUNG IKAN KERAPU BEBEK (CROMILEPTES ALTIVELIS) TERHADAP BAKTERI PATOGEN - ', Feliatra; Fitria, Yuni; ', Nursyirwani (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
Grouper fish has a fairly high economic value, especially in Asiancountries, namely Hong Kong, Singapore, Taiwan and China. High marketdemand. On aquaculture, is one important component of fish feed that plays animportant role in the cultivation. Application of probiotics in aquaculture fish feedhas not been done yet in the Fisheries sector. The research was conducted inOctober 2008, Grouper is used as the intestines and stomach samples were takenas a source of probiotics, whereas pathogenic bacteria obtained from thecollection of marine microbiology laboratory of Faculty of Fisheries and MarineRiau University. From the isolation of bacterial strains found 11 strains that havethe potential as probiotics, then proceed to the molecular test by using rDNA16 s.Which is obtained two strains of probiotic bacteria Bacillus cereus and the speciesof bacteria Strenotrophomonas maltophilia. The test results found that theantagonist Bacillus cereus isolates to inhibit the growth of pathogenic bacteriaAeromonas sp and two species of Vibrio sp. While the bacteriaStrenotrophomonas maltophilia showed no antagonism against pathogens.